2006
DOI: 10.1158/0008-5472.can-06-1052
|View full text |Cite
|
Sign up to set email alerts
|

A Repressive Epigenetic Domino Effect Confers Susceptibility to Breast Epithelial Cell Transformation: Implications for Predicting Breast Cancer Risk

Abstract: Retinoic acid (RA) is a master epigenetic regulator that plays a pivotal role in both breast morphogenesis and development. Here, we show for the first time that RA, via the RA receptor A (RARA), epigenetically regulates in a concerted fashion the transcription of two RA-responsive genes, the RA receptor B2 (RARb2) and the cellular retinol-binding protein 1 (CRBP1). Specifically, an impaired RA signal through RARA in human breast epithelial cells triggers a repressive epigenetic domino effect, involving first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 34 publications
2
51
0
Order By: Relevance
“…One of these genes is Tcfec , whose human counterpart encodes a transcription factor that induces the granulocyte colony stimulating factor receptor G-CSFR [23,24]. Remarkably, Tcfec downregulation in A16 cells is paralleled by a significant downregulation of G-csfr (data not shown), indicating that AML1-MTG16 might have triggered a coordinated cascade of transcriptional downregulation, as we observed in other differentiation model systems [37,38]. The second gene is Mgmt , encoding the DNA repair enzyme O6-Methylguanine-DNA-methyltransferase, which is frequently silenced and hypermethylated in leukemia [39].…”
Section: Discussionmentioning
confidence: 78%
“…One of these genes is Tcfec , whose human counterpart encodes a transcription factor that induces the granulocyte colony stimulating factor receptor G-CSFR [23,24]. Remarkably, Tcfec downregulation in A16 cells is paralleled by a significant downregulation of G-csfr (data not shown), indicating that AML1-MTG16 might have triggered a coordinated cascade of transcriptional downregulation, as we observed in other differentiation model systems [37,38]. The second gene is Mgmt , encoding the DNA repair enzyme O6-Methylguanine-DNA-methyltransferase, which is frequently silenced and hypermethylated in leukemia [39].…”
Section: Discussionmentioning
confidence: 78%
“…RA, after binding the nuclear receptor RARĪ±, triggers the transcription of other downstream RARs, including the RA-receptor and tumor suppressor, RARĪ²2 [6]. RARĪ²2 autoregulates its own transcription and, in turn, the transcription of a multitude of downstream RA-responsive target genes [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a loss of ATRA signaling can result in repressive methylation of downstream target genes (29,30). This, together with the lack of effect of ATRA on promoter activity, led us to explore epigenetic mechanisms of regulation, and our data clearly indicate that ATRA primarily regulates nSMase2 through directly modulating histone acetylation, which is most likely through CBP/p300.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies have reported that loss of ATRA signaling can lead to hypermethylation of downstream genes in breast epithelial cells (29,30). Moreover, the Smpd3 gene (nSMase2) is reported to be hypermethylated in some breast cancer and hepatocellular carcinoma (HCC) cells (31,32).…”
Section: The Smpd3 Gene Is Not Hypermethylated In Mcf7 Cellsmentioning
confidence: 99%